THE IMPACT OF GROUP WORK STAGES ON TEAM COLLABORATION: ANALYZING TUCKMAN’S MODEL - Che Hassan , Nor Syamimi Iliani; Mohammad Nor , Nor Hairunnisa (Journal of Islamic, Social, Economics and Development, 2024)
Group work is widely employed as a learning method across all educational levels as it encourages individuals to collaborate on completing assigned tasks. Although its benefits have been extensively documented in numerous studies, research also highlights the challenges associated with group work. To better understand effective group work strategies, Tuckman’s model, a well-known team development model is further examined. This study aims to explore the stages of Tuckman’s model in the context of team collaboration. Data were collected using questionnaires, distributed to 105 students from various study programs at a public higher learning institution in Malaysia. The descriptive analysis of the quantitative data reveals that the participants demonstrate significant levels of team collaboration across the four stages of Tuckman’s model: forming, storming, norming and performing. The result too indicates that as the group work progresses, the group members manage to overcome the internal conflicts between them and as they move on from one stage to another, the students believe that they have successfully accomplished the assigned tasks once they reach the final stage of group work. Hence, group work facilitates task completion through effective peer support, and this strategy should be integrated into teaching and learning, simultaneously, instructors should offer guidance to help learners achieve high levels of productive team collaboration.